ANALISIS AUDIT DALAM PERSPEKTIF SYARIAH - Umiyati, Umiyati; Sholikhatunnisa, Siti; Rosa, Yuanaidra Alfathia (LPPM - STIE SAKTI ALAM KERINCI, 2024)
Sharia audit is a systematic process that aims to ensure a company's compliance with Islamic laws and principles. In a sharia audit, the auditor not only examines the financial statements, but also monitors the social behavior and performance of the organization, as well as ensuring that the company has implemented all applicable economic laws, including Islamic laws and principles related to it. Sharia audits are very different from conventional audits, because the aspect of religiosity is the main foundation. Sharia audits must be expanded to include an interrelated activity. In this case, sharia auditors must understand and implement audit standards that are in accordance with Islamic principles, such as AAOIFI. Sharia auditors must also be independent and have the appropriate qualifications to conduct comprehensive and integrated audits.Sharia audit consists of several stages, including the planning stage, implementation stage, supervision stage, and reporting stage. The planning stage involves developing a clear and specific audit plan. The implementation stage involves collecting relevant data and information. The supervision stage involves supervision of the implementation of the audit plan. The reporting stage involves presenting the audit results in the form of a clear and easy-to-understand report. Keywords: Audit, Sharia Audit, Sharia Auditor, Conventional Audit